2014
DOI: 10.1186/s12879-014-0678-x
|View full text |Cite
|
Sign up to set email alerts
|

Smear plus Detect-TB for a sensitive diagnosis of pulmonary tuberculosis: a cost-effectiveness analysis in an incarcerated population

Abstract: BackgroundPrison conditions can favor the spread of tuberculosis (TB). This study aimed to evaluate in a Brazilian prison: the performance and accuracy of smear, culture and Detect-TB; performance of smear plus culture and smear plus Detect-TB, according to different TB prevalence rates; and the cost-effectiveness of these procedures for pulmonary tuberculosis (PTB) diagnosis.MethodsThis paper describes a cost-effectiveness study. A decision analytic model was developed to estimate the costs and cost-effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
8
0
2
Order By: Relevance
“…Most studies (78%) were performed in high burden TB settings, i.e. Brazil, [ 34 , 35 , 38 , 47 , 48 ] India, [ 36 , 40 , 42 , 50 , 52 , 53 ] several countries in Southern Africa (Botswana, Lesotho, Namibia, South Africa and Swaziland), [ 31 , 35 , 43 , 51 53 ] and East Africa (Kenya, Malawi, Uganda, Tanzania and Zambia). [ 30 , 35 , 41 , 44 , 46 , 49 , 51 53 , 55 ] One study performed analysis in a high burden region, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies (78%) were performed in high burden TB settings, i.e. Brazil, [ 34 , 35 , 38 , 47 , 48 ] India, [ 36 , 40 , 42 , 50 , 52 , 53 ] several countries in Southern Africa (Botswana, Lesotho, Namibia, South Africa and Swaziland), [ 31 , 35 , 43 , 51 53 ] and East Africa (Kenya, Malawi, Uganda, Tanzania and Zambia). [ 30 , 35 , 41 , 44 , 46 , 49 , 51 53 , 55 ] One study performed analysis in a high burden region, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…[ 54 ] More than half of the studies (63%) were performed within 2011–2015. [ 29 , 32 , 36 , 38 43 , 48 55 ] The earliest study dated from 1998. [ 46 ]…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the results of Detect-TB assay showed better specificity with composite diagnostic criteria when compared to laboratory criteria. In a previous study by our group, we demonstrated that smear microscopy plus Detect-TB assay was the most cost-effective initial diagnostic test for active TB when applied in a prison population with a high prevalence of active PTB, indicating that Detect-TB assay has great potential to be implemented under routine diagnostic conditions ( Schmid et al 2014 ). The overall rate of false negatives was higher when the Detect-TB assay was to composite diagnostic criteria (6.3%) than with bacteriological criteria (3.3%).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, 1 concern about this study is that almost 30% of active TB cases in this study were clinically diagnosed, and clinical assessment is not always reliable to be used as the gold standard in a comparison study. Another study that evaluated the same PCR test (Detect‐TB), and demonstrated high sensitivity and specificity, also used clinical outcome as the gold standard.…”
Section: Discussionmentioning
confidence: 99%